Different alteration patterns of sub‐macular choroidal thicknesses in aquaporin‐4 immunoglobulin G antibodies sero‐positive neuromyelitis optica spectrum diseases and isolated optic neuritis. Issue 8 (12th July 2020) - Peng, Chunxia; Li, Li; Yang, Mo; Teng, Da; Wang, Junqing; Lai, Mengying; Qian, Haiyan; Li, Hongyang; Zhou, Huanfen; Xu, Quangang; Wei, Shihui
Abstract: Purpose: The ocular choroid is a sensitive biomarker of vascular perfusion in optic neuritis (ON) patients due to its vascular structures. The purpose of this study was to evaluate alterations in sub‐macular choroidal thicknesses (sub‐MCT) in aquaporin‐4 immunoglobulin G antibodies (AQP4‐IgG) sero‐positive neuromyelitis optica spectrum disease (AQP4‐IgG+/NMOSD) and isolated ON (ION) patients using optical coherence tomography (OCT). Methods: A total of 208 ON patients (275 eyes) and healthy controls (HCs) who underwent sub‐MCT and retinal microstructure detection with OCT were enrolled in this study. Results: Among all the ON patients, 102 (49.0%) cases were identified as serum AQP4‐IgG‐positive, with 106 (51.0%) cases being negative, excluding multiple sclerosis as the ION cohort. The sub‐MCT in the AQP4‐IgG+/NMOSD patients decreased in 0–6 months after ON attacks. However, for the ION cohort, the sub‐MCT decreased in 0–2 months and then stayed normal or slightly increased in 2–4 months after the first ON attack, finally sharply decreasing after 6 months. For unilateral AQP4‐IgG+/NMOSD patients, eyes without ON also presented retinal layer thinning and sub‐MCT slight reduction independent of ON attacks. Conclusions: The sub‐MCT in AQP4‐IgG+/NMOSD patients were reduced at all stages of ON, which distinguished the ION patients as decreasing only at chronic stage of ON. It implied that ocular vascular hypoperfusion plays a potential role in ON pathogenesis and the different patterns could be caused by the distinct pathogenesis of AQP4‐IgG+/NMOSD and ION.